Un-appointed Hackers: should they be compensated? - Goliath, Yonnique Francesca (My University, 2019)
Cybersecurity and data privacy have been prioritised by financial institutions due to legislative requirements, an increase in system security breaches, and in fulfilment of their obligations to their stakeholders. This paper discusses stakeholders’ interests, the moral duties of financial institutions, and the harm caused by hacking activities, in the context of data security. Specifically, the paper seeks to answer the question whether un-appointed hackers, who alert institutions to their security vulnerabilities and do not have malicious intent, should be compensated. Stakeholders’ interests and financial institutions’ moral duties are considered in the context of the stakeholder theory, and Kantian norms. I argue that financial institutions should not compensate un-appointed hackers, because hacking violates the principle of respect due to the data subject, and the financial institution’s moral duty to act in the interests of its stakeholders.
A Research Report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Applied Ethics for Professionals Johannesburg, 2019.
Keywords: Cyberspace--Security measures--South Africa; Data protection; Privacy, Right of; Computer crimes--Prevention--Government policy.